Avaliação da produtividade de biomassa de capim elefante e sorgo sacarino no Estado do Ceará para uso energético - Pontes, Gustavo Moronta (2013)
With the growing increase in the possibilities of using biomass in various industry sectors, this study aims to identify an alternative to increase the production of biomass using elephant grass (Pennisetum purpureum) or sweet sorghum (Sorghum bicolor). The field experiments were carried out at Vitória farm (4°21'36 'S 38°5'17' W) on Beberibe, Ceará state, in a total area of 1,944 m2. Trees were planted in 36 randomized plots of 54 m2 using completely randomized statistical design, with 9 treatments (genotypes) and 4 replications. It was studied six different genotypes of sorghum, s_1, s_2, s_3, s_4, s_5 and s_6. A hybrid of elephant grass with millet (Pennisetum glaucum) commercially known as ‘paraíso’ cultivar and two treatments of elephant grass, Cameroon and Napier also took part in this study. For sorghum, 3 harvests were performed, in which the first was evaluated weekly and the others on one occasion. The elephant grass had two harvests, the first with an interval of 186 days and the second with a period of time of 92 days. The difference of days allowed the comparison of biomass productivity in each treatment in an interval of three and six months. The results showed that the most prominent treatments of biomass productivity were those with elephant grass, regardless of the harvest period, if three or six months. Based on this information, it was concluded that by analyzing only the biomass productivity the most suitable of the treatments studied is the elephant grass, Napier or Cameroon that statistically showed no significant difference. However, sweet sorghum presented a high productivity when it was used with a supplement, in a mixture that can be used in order to produce ethanol.